Lessons from New York High Line Green Roof: Conserving Biodiversity and Reconnecting with Nature - Kawar Salih; Zaid O. Saeed; Avar Almukhtar (Urban Science, 2021)
The concept of sustainable urban design has appeared in different perspectives to minimize and reduce the negative impacts of urban expansion in terms of climatic and environmental drawbacks. One of the undeniable approaches of sustainable urban design is the adoption of green urban roofs. Green roofs are seen to have a substantial role in addressing and resolving environmental issues in the context of climate change. Research investigations have indicated that green roofs have a remarkable impact on decreasing rainwater runoff, reducing the heat island effect in urban spaces, and increasing biodiversity. Nevertheless, green roofs in urban spaces as a competent alternative to nature remains a standing question. To what extent can green roofs mimic the biodiversity that is seen in nature? Moreover, to what level is this approach practical for achieving a tangible reconnection with nature, or so-called biophilia? This study attempts to discuss the essence and impact of green roofs in urban spaces based on a case study approach. The study reflected lessons from the New York High Line Green Roof regarding biophilia and biodiversity in this case study. It concludes with key lessons that can be transferred to other urban spaces with similar settings.